KAJIAN LAFAZ DARI SEGI PENGGUNAAN MAKNA: ANALISIS HAQIQAH DAN MAJAZ SERTA IMPLIKASINYA DALAM ISTINBATH HUKUM ISLAM - Sri Wahyuni Kasim; Abdul Syatar; Fatmawati (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2026)
The study of linguistic expressions (lafaz) in Islamic legal theory (ushul fiqh) plays an important role in understanding the meanings of the Qur’an and Hadith as the primary sources of Islamic law. One of the linguistic aspects discussed by Muslim scholars is the use of meaning through haqiqah (literal meaning) and majaz (figurative meaning). This study aims to analyze the concepts of haqiqah and majaz, explain their position in understanding Islamic legal texts, and examine their implications for the process of legal deduction (istinbath al-ahkam). This research employs a library research method with a descriptive-analytical approach by reviewing relevant literature in ushul fiqh, Qur’anic exegesis, and academic journals. The findings indicate that literal meaning should be prioritized in interpreting a text, while figurative meaning may be applied when supported by clear contextual evidence.